Analisis Dampak Kepribadian Introvert Terhadap Perkembangan Diri Remaja: Tinjauan Psikologis - Ahmad Royani; Nadya Nailal Husna (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2024)
Introverted personality is often misunderstood as a weakness in social abilities. However, adolescents with this personality type possess great potential in self-reflection, emotional intelligence, and academic achievement. This study aims to analyze the psychological impact of an introverted personality on adolescent self-development, particularly in the context of Madrasah Aliyah KHAS Kempek. A descriptive qualitative method was employed, involving in-depth interviews and observations of several female students with introverted tendencies. The findings indicate that introverted individuals face challenges in social interactions and self-confidence, yet excel in self-regulation, perseverance in learning, and critical thinking skills. This study underscores the need for more responsive and inclusive educational strategies that cater to the characteristics of introverted personalities to help maximize their potential.